PENERAPAN RAGAM HIAS MINANGKABAU DALAM PEMBELAJARAN MEMBATIK BAGI GURU SENI BUDAYA SMPN DAN MTsN KABUPATEN PADANG PARIAMAN - Syafei Syafei; Efrizal Efrizal; Yasrul Sami; Zubaidah Zubaidah; Ariusmedi Ariusmedi; Maltha Kharisma (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2021)
One of the obstacles in improving the quality of education and learning in schools is the lack of improvement in the quality of teachers. In addition, the limited opportunity to gain additional knowledge and skills for teachers is the cause of the decline in the quality of education. The results of the instructor team's discussion with Desmiyanti, S, Pd. a teacher in the field of Fine Arts Studies at SMPN 2 VII Koto Sungai Sariak, Padang Pariaman Regency (2020) that: the implementation of Fine Arts learning at SMPN Padang Pariaman Regency is on average taught by teachers with educational backgrounds other than Fine Arts. One indication shows the low ability of teachers in batik learning materials that require theory and practice of standard materials and equipment and procedures. As a consequence, the learning of fine arts, especially batik material, does not work properly. Especially if it is related to batik materials and equipment, the average junior high school level has received subsidies from the education office. However, in reality, teachers are not able to utilize the materials and equipment of batik that are already available for learning fine arts. Concerns about the inability of teachers in the learning process, especially this batik material, require teachers to attend education and training/workshops on: